Tripterygium glycosides: recent advances in mechanisms, therapeutic applications, and safety optimization - Jin, Yujie; Cui, Yongxin; Zhang, Zhanyan; Huang, Chenglin; Tong, Ruoting; Ling, Ye; Pei, Qirui; Ma, Yan; Zhan, Qixia; Leng, Xiaojian; He, Junjun; Wang, Lizhuo; et al. (Frontiers in Medicine, 2026)
Tripterygium glycosides (TG), bioactive extracts derived from Tripterygium wilfordii Hook F., possess potent anti-inflammatory and immunomodulatory properties, making them promising therapeutic candidates for a range of autoimmune and inflammatory diseases. This review summarizes recent advances in the pharmacological mechanisms of TG, including their roles in cytokine suppression, autophagy modulation, anti-fibrotic remodeling, and oxidative stress regulation. Evidence from clinical trials and real-world studies supports the therapeutic potential of TG in conditions such as systemic lupus erythematosus, diabetic kidney disease, rheumatoid arthritis, and psoriasis. In addition, we highlight ongoing efforts to overcome TG's narrow therapeutic window through monomer isolation, structural optimization, prodrug strategies, and innovative delivery systems. Emerging derivatives—such as LLDT-8 (5R-5-hydroxytriptolide) and triptonide—exhibit reduced toxicity while retaining robust efficacy, providing new avenues for clinical translation. Furthermore, the integration of systems pharmacology, synthetic biology, and AI-assisted drug design is accelerating the development of next-generation TG-based therapeutics.